RELASI GENDER DAN KEKUASAAN DALAM ISLAM INDONESIA - Yuberti, Yuberti (Analisis: Jurnal Studi Keislaman, 2015)
THE GENDER RELATIONS AND POWERS OF ISLAM IN INDONESIA:  This paper is a review of a book entitled  Gender and Power  in Indonesian Islam:  Leaders,  Feminists,  Sufis  and Pesantren Selves, edited by Bianca J. Smith and Mark Woodward published by Routledge, London and New York in 2014. This book examines the surrounding gender and development  of the role of women  in Indonesia,  in terms  of leadership, religious  politics, feminism, mysticism and its influence in Indonesia, especially the world of boarding schools. This book is brave enough to revealed the theme  about  the issue of gender namely in pesantren.  Like challenge  the  tiger  in its  cage. However,  in contrast  to gender studies written  by Westerners in general, this book is certainly a protagonist  and not hostile the Moslem such as the masterpiece of the Western people over the years. In addition,  the book also involves some local writers.  Most other Western  writers submit data  Indonesian  Islamic studies  in private  in the  sense of self- written. This is a new approach in the study of the contemporary orientalism  which increases the load Islamic studies objectively. However,  Islamic  studies   who  stuck  around  women  in this book still  feel mono-paradigm  though  written  by the East  side (Indonesia) and the West side. Therefore, the gender paradigm is used to show the impression of partiality  Islam against women at the same time which is practiced  in the involvement  of women on the  political  sphere leadership  and  Sufism  in Lombok  and Aceh which still  depart  from the paradigm  of Western  gender. In fact, the version of the typical domestic and gender approach demonstrated  that women has the balance position with men and women can take the fight against the men domination as the echo from the western version idea about the gender.